Cognitive agency in music interventions: Increased perceived control of music predicts increased pain tolerance. (6th May 2021) - Howlin, Claire; Rooney, Brendan
Abstract: Background: Self‐selected music is consistently found to be the strongest predictor for successful music listening interventions in pain management contexts, but the specific cognitive mechanisms that mediate these effects are currently unknown. Objectives: The aim of this study was to isolate the role of cognitive agency on pain tolerance in music listening interventions, independently from parallel effects related to enjoyment. Additionally, the study examines the role of intramusical features and individual attributes related to musical engagement. Methods: Fifty‐two participants completed a repeated measures experiment, which involved listening to six different pieces of music while completing the cold pressor task. Cognitive agency was operationalized by giving participants different degrees of perceived control over the music selection, when in fact it was pre‐determined by the experimenter. Results: A generalized linear mixed model was used to analyse the impact of perceived choice and intramusical features on pain tolerance measured in terms of duration on the cold pressor task, pain intensity and pain unpleasantness. Increased levels of perceived choice predicted increases in pain tolerance when enjoyment was accounted for. Individual levels of trait empathy and sophisticated emotional engagement with music also contributed to the effects. Intramusical features did not predict increases in pain tolerance. Conclusions: This study demonstrates that the reason self‐selected music is particularly effective in reducing pain is related to the act of making a choice over the music itself. This study provides support for the cognitive vitality model and emphasizes the importance of giving people as much control as possible in music interventions. Significance: This study identifies that the act of selecting music contributes to increases in pain tolerance in parallel with the independent factor of enjoyment. This provides support for the role of cognitive agency in mediating the analgesic effects of music interventions, which suggests that people should be given as much control as possible in music interventions. Additionally, this study identifies specific individual attributes related to emotional engagement and empathy that amplify the effect of cognitive agency.